2020
DOI: 10.1097/txd.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gut Microbiome in Liver Transplant Recipients With Nonalcoholic Steatohepatitis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…A meta-analysis of four RCTs [141] found that the synergic use of prebiotics and probiotics significantly reduced the infection rates (7% vs. 35%) after LT; these results were later confirmed by a fifth RCT [137]. Moreover, gut dysbiosis was also associated with the development of non-anastomotic biliary strictures [142], hepatic generation after partial liver grafts [132], and the recurrence of liver disease [143].…”
Section: Faecalibacterium Lachnospiramentioning
confidence: 94%
“…A meta-analysis of four RCTs [141] found that the synergic use of prebiotics and probiotics significantly reduced the infection rates (7% vs. 35%) after LT; these results were later confirmed by a fifth RCT [137]. Moreover, gut dysbiosis was also associated with the development of non-anastomotic biliary strictures [142], hepatic generation after partial liver grafts [132], and the recurrence of liver disease [143].…”
Section: Faecalibacterium Lachnospiramentioning
confidence: 94%
“…Besides, there is a relative abundance of potential pathogens, such as Gram-negative Proteobacteria, Enterobacteriaceae, and Escherichia spp. among patients with NASH, when compared to healthy controls, while Faecalibacterium prausnitzii and Akkermansia muciniphila are relatively diminished [ 33 , 34 , 35 ]. Faecalibacterium prausnitzii , a Gram-positive anaerobe bacterium, Eubacterium rectale , Eubacterium halii , and Anaerostipes caccae are well-known short-chain fatty acids (SCFAs) producers, particularly butyrate.…”
Section: Nafld Gut Dysbiosis and Microbial Signaturesmentioning
confidence: 99%
“…Akkermansia muciniphila , a mucin-producing, Gram-negative anaerobe bacterium, when co-cultured with the butyrate-producing Faecalibacterium prausnitzii , Eubacterium rectale , Eubacterium halii , and Anaerostipes caccae results in an enhanced production of butyrate. Therefore, Akkermansia muciniphila , apart from its beneficial role in the gut epithelium per se, may promote the growth of other bacteria with anti-inflammatory properties [ 33 , 34 , 35 ]. Children with NAFLD and NASH have a decreased proportion of Oscillospira spp.…”
Section: Nafld Gut Dysbiosis and Microbial Signaturesmentioning
confidence: 99%
“…Satapathy SK et al found loss of AKM in patients after LT, especially in patients with recurrent NAFLD. It has been suggested that AKM may play a protective role in the development of complications (such as de novo NAFLD) after LT [20]. However, Sun et al, found an increase in potentially beneficial bacteria, such as AKM, Blautia and Clostridiales cluster XIVa, 3 months after LT.…”
Section: Discussionmentioning
confidence: 99%